2016
DOI: 10.1016/j.scitotenv.2016.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the sorption of polybrominated diphenyl ethers (PBDEs) to cotton and polyester fabrics under controlled conditions

Abstract: Cotton and polyester, physically and chemically different fabrics, were characterized for sorption of gas-phase polybrominated diphenyl ethers (PBDEs). Scanning electron microscopic (SEM) images and BET specific surface area (BET-SSA) analysis showed cotton's high microsurface area; NMR analysis showed richness of hexose- and aromatic-carbon in cotton and polyester, respectively. Cotton and polyester sorbed similar concentrations of gas-phase PBDEs in chamber studies, when normalized to planar surface area. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…This is surprising given that lower polarity PCBs might be expected to have a greater affinity for low‐polarity polyester. For brominated diphenylethers (BDEs) sorbing to cotton and polyester in laboratory chambers, Saini et al observed higher mass‐normalized distribution coefficients for polyester than cotton. However, they noted that these materials may not have been at equilibrium because, in part, there was little difference between distribution coefficients normalized by planar surface area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising given that lower polarity PCBs might be expected to have a greater affinity for low‐polarity polyester. For brominated diphenylethers (BDEs) sorbing to cotton and polyester in laboratory chambers, Saini et al observed higher mass‐normalized distribution coefficients for polyester than cotton. However, they noted that these materials may not have been at equilibrium because, in part, there was little difference between distribution coefficients normalized by planar surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Models that predict the impact of clothing on dermal uptake have been developed but require knowledge of the sorptive capacity of the clothing and its exposure history prior to being worn. Accumulation of organic compounds with clothing fabrics has been quantified using laboratory chambers, inferred from dynamic uptake experiments and from fabrics exposed to air in an office . The latter method best assesses the accumulation under real‐world environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the influence of chemical properties of the sorbing chemical and fibers, the physical properties of the fibers can also influence sorption. For example, natural fibers such as cotton (cellulose) and wool (protein) tend to have large and irregular surface areas and a porous structure that favors entrapment of particles compared to synthetically derived and spun fibers such as polyester and rayon (rayon is synthetically spun cellulose) inter alia .…”
Section: Introductionmentioning
confidence: 99%
“…Saini et al 20 found that gas-phase non-polar polybrominated diphenyl ethers (PBDEs) sorption was similar to cotton and polyester when expressed on a planar surface area basis. From this, they concluded the uptake was air-side limited and not influenced by the chemical characteristics of the fabric polymer.…”
mentioning
confidence: 99%
“…Clothes, which often contain skin oil, have been shown to remove significant amounts of O 3 indoors and are important for the uptake of semi-volatile organic compounds (SVOCs), which can be accumulated on and released from clothes [21][22][23][24][25][26] . Measurements have shown that a single soiled t-shirt can account for 70% of the total O 3 removed by a person 27 .…”
mentioning
confidence: 99%